Association of Upstream Transcription Factor 1 Gene (USF1) rs3737787 with Reduced LDL (low-density lipoprotein) Cholesterol Level among Iban Ethnic Groups in Sarawak Population - Mohd Aminudin, Mustapha; Sim, Sai-Peng; Hafizah Hanis, Hood; Siaw, Yun Ted (Japan University of Health Sciences & Japan International Cultural Exchange Foundation, 2021)
Objective: to determine the polymorphic allele and genotype frequencies of USF1 rs3737787. It aimed to elucidate the association of the polymorphic allele and genotypes with clinical profiles such as total cholesterol (TC), high- density lipoprotein (HDL), low- density lipoprotein (LDL) and homocysteine level in Iban ethnic group in Sarawak. Materials and Methods: One hundred and fifteen (115) individuals of the Iban ethnic group were recruited as the study subjects. The Allele Specific PCR (AS-PCR) was used in the genotyping. Association of genotype frequencies and clinical profile was assessed using One Way ANOVA. As for the association of allele frequencies and clinical profile, Independent Sample T test was used. Results: Genotype frequency showed statistical significant difference between genotypes of Upstream Transcription Factor 1 (USF 1) rs3737787 with low-density lipoprotein (LDL) level with p value of 0.035. The wildtype and heterozygous genotypes of USF 1 rs3737787 is significantly associated with low level of LDL with F (1,113) = 4.551, p < 0.05. Conclusion: Our results show that the genetic diversity of USF1 rs3737787 influences the susceptibility to decreased level of LDL in the Iban ethnic group of the Malaysian population.